A requirement for Krüppel Like Factor‐4 in the maintenance of endothelial cell quiescence - Mastej, Victoria; Axen, Cassondra; Wary, Anita; Minshall, Richard D.; Wary, Kishore K. (Frontiers in Cell and Developmental Biology, 2022)
Endothelial cells (ECs) are quiescent and critical for maintaining homeostatic functions of the mature vascular system, while disruption of quiescence is at the heart of endothelial to mesenchymal transition (EndMT) and tumor angiogenesis. Here, we addressed the hypothesis that KLF4 maintains the EC quiescence. In ECs, KLF4 bound to KLF2, and the KLF4-transctivation domain (TAD) interacted directly with KLF2. KLF4-depletion increased KLF2 expression, accompanied by phosphorylation of SMAD3, increased expression of alpha-smooth muscle actin (αSMA), VCAM-1, TGF-β1 and ACE2, but decreased VE-cadherin expression. In the absence of Klf4, Klf2 bound to the Klf2-promoter/enhancer region and autoregulated its own expression. Loss of EC-Klf4 in Rosa(mT/mG)::Klf4(fl/fl)::Cdh5(CreERT2) engineered mice, increased Klf2 levels and these cells underwent EndMT. Importantly, these mice harboring EndMT was also accompanied by lung inflammation, disruption of lung alveolar architecture, and pulmonary fibrosis. In quiescent ECs, KLF2 and KLF4 partnered to regulate a combinatorial mechanism. The loss of KLF4 disrupted this combinatorial mechanism, thereby upregulating KLF2 as an adaptive response. However, increased KLF2 expression overdrives for the loss of KLF4, giving rise to an EndMT phenotype.